Preoperative Biliary Drainage of Jaundiced Patients with Pancreatic Head Cancer: A Routine or Selective Strategy - Tshijanu, Fernand; Xiarchos, Anastasios (Highlights on Medicine and Medical Research Vol. 9, 2021)
Most patients with pancreatic head cancer (85%) are jaundiced at presentation. Obstructive jaundice is thought to increase the risk of perioperative and postoperative complications. According to some experimental and clinical studies, preoperative biliary drainage (PBD) improves postoperative outcomes. However, numerous randomized studies found that PBD might increase postoperative complications rate. Thus, PBD or not is controversial. Objective: To confirm if PBD can be a routine or selective strategy in these patients. Material and Methods: A retrospective study comparing PBD with surgery alone in 200 jaundiced patients with pancreatic head cancer from 2nd Department of Surgery-Hellenic Red Cross Hospital of Athens (1996-2011). Data from patient’s files including: Age, gender, smoking, diabetes history, Laboratory parameters, procedures, post-operative course. Results: The majority of patients (62.5%) were males, with adenocarcinoma (93.5%), smokers (65.0%), and half of them were diabetics. The median age was 70 years, median tumor size was 5 cm, while PBD was performed in 74 patients (37.0%) with higher laboratory parameters (Direct bilirubin 18 mg/dl vs 13 mg/dl. Total bilirubin 24 mg/dl vs 20 mg/dl) and in this group was marked: higher postoperative complications rate, higher ICU admission rate, higher postoperative mortality (17.6% vs 5.6%). Conclusion: We believe that PBD should be a selective strategy in jaundiced patients with pancreatic head cancer in case of fever, non- operability of patients, and in case of more advanced disease as a palliative alternative since, this method increases postoperative complications rate.